The Managing Director's Global Policy Agenda : Rising Risks: A Call for Policy Cooperation. (Policy Papers; Policy Paper ;, 2018)
Global growth remains strong. The recovery has created jobs and increased incomes. But growth momentum is moderating. Previously identified risks have partly materialized or have become more pronounced. A rapid reversal in financial market conditions, ten years after the global financial crisis, could again expose debt vulnerabilities at a time when many countries have more limited policy space. The window of opportunity to guard against risks and raise medium-term growth prospects is narrowing. Now is the time for policymakers to act to rebuild policy space, strengthen resilience, and implement structural reforms for the benefit of all. Waning support for multilateralism is fueling policy uncertainty. However, improved global cooperation is precisely what is needed to boost inclusive growth by modernizing the trade system, reducing excess global imbalances, improving debt dynamics, and leveraging technology. We will continue to review our policies and strategies to enhance Fund advice and support multilateralism. This includes surveillance, program conditionality, capacity development, debt limits, and anti-money laundering and the combatting of terrorism financing.